Employment, chronic disease prevalence and medical care among the older population in India: an assessment of linkages. (3rd June 2014) - Namdevrao Yadav, Priyanka; Goli, Srinivas; Perianayagam, Arokiasamy; Maikho Apollo Pou, Ladumai
Abstract : Purpose: – The purpose of this paper is to examine the linkages of employment, chronic disease prevalence and medical care of the older population in India. Design/methodology/approach: – This study used the India Human Development Survey data for the analysis. Bivariate, multinomial logit regression and multiple classification analysis are used as methods for the study. Findings: – The findings suggest a bi-directional relationship between employment and chronic diseases: the older population who are engaged in regular paid work has lower likelihood to the risk of chronic diseases compared to those who are not working. Conversely, the older population with chronic diseases may be unable to work in regular paid jobs. The greater proportions of not-working older population with savings and retirement pensions are more likely to seek modern treatment for the chronic diseases. Overall, the results foster that employment determines and is determined by chronic disease prevalence among the older population in India. Originality/value: – This paper for the first time presents evidence on the linkages of employment, chronic disease prevalence and medical care of the older population in India by using a unique and comprehensive data source.